EXPERIMENTAL STUDY OF THE DEGRADATION OF THE PESTICIDE METOMIL IN SURFACE WATERS APPLYING ADVANCED OXIDATION PROCESSES - Bernal de Arenas, Miriam (2021)
The intensive use of agrochemicals for food production in developing countries has generated a problem of environmental concern since many of these substances, which are usually difficult to biodegrade, can reach natural sources, generating their contamination. That is why the search for new technologies for the elimination of these pollutants has arisen with great interest. Advanced oxidation processes (AOP), whose main characteristic is the generation of highly oxidizing species such as the hydroxyl radical, can achieve the chemical modification of the pollutant, generating by-products that can be less harmful to the environment. In this work, the degradation of methomyl, a highly used insecticide in the Arequipa region, Peru, was evaluated using different PAOs such as ozonation in alkaline medium, UV-C/H2O2 and photo-Fenton processes at acid pH in natural surface waters. The effect of anion matrix such as bicarbonates, fluorides and nitrates were evaluated on a laboratory scale and later in natural surface waters. The results indicate that the highest methomyl removal in real water was achieved at 99.38% for UV-C/H2O2 followed by the photofenton process, with 94.12% degradation and ozonolysis at alkaline (pH 11) with 40% degradation, demonstrating that the evaluated PAOs can be a promising alternative to eliminate agrochemicals from natural sources.